2021
DOI: 10.1177/08862605211028006
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Discrimination Experiences in Postrape Adjustment Among Racial and Ethnic Minority Women

Abstract: Although recent studies have linked discrimination frequency among Black and Latinx individuals to PTSD symptom severity, to our knowledge, these associations have yet to be examined among a diverse sample of recent rape survivors. The current secondary analysis of existing data examined the role of discrimination experiences in post-traumatic stress disorder (PTSD) symptoms, depression, and alcohol and drug problems among a racially and ethnically diverse sample of recent rape survivors. Participants were 139… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…Each of the PHC clinics identified that those they served often faced poor treatment when accessing care at local EDs. These findings aligned with historical and ongoing evidence of inequitable treatment in EDs for Indigenous people [4,7,33,34], people experiencing violence [35,36], and those presenting with histories of mental illness [37], substance use and/or homelessness [38,39].…”
Section: Introductionsupporting
confidence: 68%
“…Each of the PHC clinics identified that those they served often faced poor treatment when accessing care at local EDs. These findings aligned with historical and ongoing evidence of inequitable treatment in EDs for Indigenous people [4,7,33,34], people experiencing violence [35,36], and those presenting with histories of mental illness [37], substance use and/or homelessness [38,39].…”
Section: Introductionsupporting
confidence: 68%
“…Similar to previous studies (Salas -Wright et al, 2015-Wright et al, , 2018, items were dichotomized such that participants who reported never or almost never experiencing any form of discrimination were coded as 0 (did not report discrimination in the past year) and those who reported sometimes, fairly often, and very often for any item as 1 (reported experiencing discrimination in the past year). This scale has been applied to Latin American immigrants (Hosler et al, 2019;Walsh et al, 2022).…”
Section: Discriminationmentioning
confidence: 99%
“…Women are almost twice as likely as men to develop posttraumatic stress disorder (PTSD) after a traumatic event (Shansky, 2015). For women from racial and ethnic minority groups, higher base rates of certain index traumas (Frieden et al, 2014) and the likelihood of experiencing traumatic sequelae from racial and ethnic discrimination present additional vulnerabilities associated with increased rates of PTSD (Fani et al, 2021; Walsh et al, 2021). Veteran women are twice as likely as civilian women to have PTSD (Lehavot et al, 2018), due primarily to a greater likelihood of childhood trauma and exposure to military service-related trauma (e.g., combat; military sexual trauma [MST]; Katon et al, 2015).…”
Section: Introductionmentioning
confidence: 99%